Influence of thermal conductivity on the dynamic response of magnetocaloric materials. (November 2015) - Porcari, G.; Morrison, K.; Cugini, F.; Turcaud, J.A.; Guillou, F.; Berenov, A.; van Dijk, N.H.; Brück, E.H.; Cohen, L.F.; Solzi, M.
Highlights: The time constant of temperature change offers information about the material's properties. The passive matrix in the composites affects both the MCE and its time constant. Silver addition in LCMO enhances the material's response to the outer field sweep. The material's thermal conductivity is the dominant factor for the time constant of temperature change. Abstract: We compare the magnetocaloric effect of samples prepared with different thermal conductivities to investigate the potential of composite materials. By applying the magnetic field under operating conditions we test the material's response and compare this to heat transfer simulations in order to check the reliability of the adiabatic temperature change probe used. As a result of this study we highlight how the material's thermal conductivity influences τ, the time constant of temperature change. This parameter ultimately limits the maximum frequency of a refrigerant cycle and offers fundamental information about the correlation between thermal conductivity and the magnetocaloric effect.